A Review of Bekasi City (West Java, Indonesia) Regional Archives and Library Office Service Transformation Policy Strategy - Hamudy, Moh Ilham A; Rifki, M Saidi (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2024)
Background: This study analyzes the Bekasi City Regional Archives and Library Office ‘s organizational management issues, specifically budget and human resources. The analysis applies Philip Kohler's organizational management theoryObjective: The study is motivated by challenges in optimal budget absorption, misallocation of funds, and human resource constraints, all of which impact the effectiveness of library services. The primary objective is to develop policy strategies to address these issues, particularly to promote reading habits and a culture of literacy in the communityMethods: The study employed a descriptive qualitative method incorporating interviews, observations, focus group discussions (FGDs), surveys, and document analysisResults: Findings indicated continuous staff training, improved communication and coordination, and innovative library programs are crucial for enhancing budget and human resource efficiency and effectivenessConclusion: In conclusion, targeted policy strategies can overcome existing barriers, foster improvements in the Community Literacy Development Index (IPLM) and Reading Interest Level (TGM), and help the organization achieve its strategic goals